Beyond the Impact Factor: Reflecting on Twenty Years of Leading Efforts in Research, Innovation in Publishing, and Investment in People - Torous, John (JMIR Publications, 2019)
This viewpoint celebrates the accomplishments of the Journal of Medical Internet Research (JMIR) on its twentieth anniversary and reviews accomplishments around research publications, journal innovation, and supporting people.